Kidney Cancer Incidence and Mortality Disparities Involving American Indians/Alaska Natives: An Analysis of the Oklahoma Central Cancer Registry (OCCR). (19th June 2022) - Gonzalez, Victoria; Suflita, Michael; Janitz, Amanda; Campbell, Janis; McIntosh, Andrew G.; Stratton, Kelly; Cookson, Michael S.; Parker, Daniel C.
Abstract : Purpose . This cohort study describes the differences in kidney cancer age-adjusted incidence and mortality rates between American Indians/Alaskan Natives (AI/ANs) and Whites in Oklahoma. Additionally, rates for the U.S. are updated to establish an epidemiological comparison between Oklahoma and the rest of the country. Materials and Methods . Kidney cancer age-adjusted incidence and mortality rates for Oklahoma were gathered using the Oklahoma Central Cancer Registry since 1999. National rates were obtained from the Center for Disease Control and Prevention Wide-ranging Online Data for Epidemiologic Research database between 1997 and 2017. Rate ratios were used to compare incidence and mortality rates for AI/ANs and Whites within Oklahoma as well as the entire country. Joinpoint regression models were created to illustrate trends in kidney cancer incidence and mortality. Results . The age-adjusted incidence rate of kidney cancer in Oklahoma for AI/ANs and Whites was 32.3 and 15.8 per 100, 000, respectively, for an incidence rate ratio of 2.04. The national incidence rate ratio was 0.89. The age-adjusted mortality rate in Oklahoma for AI/ANs and Whites was 9.78 and 4.98 per 100, 000, respectively, for a mortality rate ratio of 1.98. Oklahomans, irrespective of race, fare worse in terms of kidney cancer mortality compared to the rest of the country. Conclusions . In Oklahoma, AI/ANs are more likely than Whites to have a kidney cancer diagnosis. AI/ANs are twice as likely to die from kidney cancer than Whites in Oklahoma. AI/AN populations in certain states may benefit from kidney cancer early screening initiatives.